PENGARUH CORPORATE GOVERNANCE DAN FAKTOR LAINNYA TERHADAP TAX AVOIDANCE - Ramadhanti, Tania Larissa; Marlinah, Aan (E-Jurnal Akuntansi TSM, 2023)
This research was conducted to obtain empirical evidence regarding the influence of the independent variables on the dependent variable. The independent variables used in this study are institutional ownership, independent commissioners, audit committees, audit quality, profitability and sales growth. While the dependent variable in this study is tax avoidance. This research is a quantitative research that uses secondary data sources obtained from the company's financial statements. The research object used in this study is a manufacturing company listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique used in this study was purposive sampling with 6 research sample criteria that had been determined so that a total sample of 73 companies or 219 research data was obtained. This study uses multiple regression methods to analyze the data. The results of this study indicate that the audit committee variable (KOM) has a positive influence on the Effective Tax Rate (ETR) or a negative effect on tax avoidance and the profitability variable (ROA) has a negative influence on the Effective Tax Rate (ETR) or a positive effect on tax avoidance. Meanwhile, institutional ownership, independent commissioners, audit quality, and sales growth variables have no effect on tax avoidance.